2019
DOI: 10.1101/721134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical Risk Factors for Post Traumatic Stress Disorder (PTSD) in Recent Trauma Survivors

Abstract: Background: Low hippocampal volume could serve as an early risk factor for Post-traumatic Stress Disorder (PTSD) in interaction with other brain anomalies of developmental origin. One such anomaly may well be a presence of large Cavum Septum Pellucidum (CSP), which has been loosely associated with PTSD. Here, we performed a longitudinal prospective study of recent trauma survivors. We hypothesized that at one-month after trauma exposure, the relation between hippocampal volume and PTSD symptom severity will be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…An intermediary point of 6-months post-trauma might be too early to capture the tangible chronic PTSD subtype, whereas 14-months may portray a more stable representation of the chronic disorder, as it was shown to predict over 90% of the expected recovery from PTSD 113,114 . A similar trend of null-results at TP2 was observed in a previous analysis of this data set examining neuroanatomical risk factors for PTSD 115 .…”
Section: Contribution Of Early Neural Functionality Of Nvs and Pvs To...supporting
confidence: 88%
“…An intermediary point of 6-months post-trauma might be too early to capture the tangible chronic PTSD subtype, whereas 14-months may portray a more stable representation of the chronic disorder, as it was shown to predict over 90% of the expected recovery from PTSD 113,114 . A similar trend of null-results at TP2 was observed in a previous analysis of this data set examining neuroanatomical risk factors for PTSD 115 .…”
Section: Contribution Of Early Neural Functionality Of Nvs and Pvs To...supporting
confidence: 88%
“…It is worth noting that our resting state connectivity patterns were less significant at T2. Nevertheless, as was shown in previous work ( Ben-Zion, Artzi, Niry, Keynan, Zeevi, et al., 2019 , Ben-Zion, Shany, Admon, Keynan, Avisdris, Balter, Shalev, Liberzon, Hendler ), it might be explained by the dynamic clinical manifestations during the first critical year after trauma ( Hepp et al., 2008 ), in which an intermediary point of six-months might be too ”noisy” to isolate chronic PTSD symptom cluster. This is also supported by similar results in previous work examining structural abnormalities in this cohort ( Ben-Zion et al., 2019a ), as well as the lowered prediction results at Table 2 , Table 3 , Table 4 for T2.…”
Section: Discussionmentioning
confidence: 89%
“…The development of PTSD in a subgroup of survivors, and the tenacity of the protracted disorder, suggest a long-lasting trauma induced neuro-behavioral alteration ( Pitman et al., 2012 ). Longitudinal studies examining multi-modal dimensions of the response to trauma (e.g., symptoms, cognitive functions, brain structure and functioning) are optimally suited to detect the underlying neuro-behavioral moderators of non remitting PTSD ( Ben-Zion, Artzi, Niry, Keynan, Zeevi, et al., 2019 , Ben-Zion, Fine, Keynan, Admon, Green, Halevi, Fonzo, Achituv, et al., 2018 , Pitman, Rasmusson, Koenen, Shin, Orr, Gilbertson, Milad, Liberzon, 2012 , Shalev, Liberzon, Marmar, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found a trend suggesting that RSFC between the amygdala and hippocampus was strengthened post-therapy, particularly in the left hemisphere (Figure 3). Prior work suggests that modulation of amygdalae-hippocampal RSFC may be an important component of MDMA-AT for PTSD (43,(51)(52)(53)(54)(55), thus investigating this connection in future studies is warranted. We also found participants had increased activation in areas involved with self-referential processing and autobiographical memory while listening to traumatic versus neutral memory narrations pre-therapy (Figures 4A-D), and that no significant contrast existed after MDMA-AT (Figure 4E).…”
Section: Discussionmentioning
confidence: 99%
“…Sripada et al (43) found combat veterans with PTSD have decreased amygdala-hippocampal resting-state functional connectivity (RSFC) compared to combat veterans without PTSD, which the authors speculate may represent an inability to contextualize affective information in PTSD. Increased amygdala-hippocampal RSFC following stress/trauma exposure has been shown to correlate with recovery from stress or trauma symptoms (51)(52)(53), suggesting a possible adaptive mechanism to threat exposure. In healthy volunteers, the acute administration of MDMA increases amygdala-hippocampal RSFC (54).…”
Section: Introductionmentioning
confidence: 99%